NHS jobs : using digital platforms to transform recruitment across the English & Welsh National Health Service - Thompson, Mark (Writer on economics) ([London] : SAGE, 2016)
Recruitment within the UK's National Health Service (NHS), Europe's largest employer, had become outdated, expensive and inefficient. Written by someone with first-hand involvement, this case study explores how a digital platform, NHS Jobs, was successfully introduced which completely transformed the recruitment activities of over 650 NHS employers across the country, saving the government D1bn and improving the service for both employers and applicants alike.
Originally Published in: Thompson, M. (2015). NHS Jobs: Using digital platforms to transform recruitment across the English & Welsh National Health Service. Cambridge: University of Cambridge, Judge Business School.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Great Britain. -- National Health Service; Employees -- Recruiting -- Case studies